OCUPAÇÃO DE CONCHAS DE GASTRÓPODES POR ERMITÕES (CRUSTACEA, DECAPODA, ANOMURA) NA PRAIA DA LAGOINHA, BOMBINHAS, SC - Paluski, Geovana Bastos (2019)
The diversity of environments occupied by hermit crabs and their great riches makes them the object of favorable studies to understand the organization of the community of marine invertebrates, including evolutionary mechanisms. The present study tested the hypothesis that hermit crabs select shells available because of the morphometric variables they have, thus demonstrating the selection of the hermit on certain species of shells. For this, four collections were carried out over a year, at Lagoinha Beach, in Bombinhas City, Santa Catarina State, Brazil. In order to evaluate possible relationships between hermit crabs and their occupied shells, correlations were plotted between hermit weight and shell weight, length and width of the hermit's cephalothorax, and length and width of shell opening. The hermits were identified and classified in males, females, ovigerous females and intersex. Six species of hermit crabs were sampled: Pagurus brevidactylus (n = 644); Clibanarius antillensis (n = 613); Pagurus criniticornis (n = 600); Calcinus tibicen (n = 36); Paguristes tortugae (n = 2); Clibanarius vittatus (n = 1). The occupied shells totaled 22 species. This research accepted the hypothesis that hermit crabs select shells available in the environment by morphometric attributes. Species of the genus Pagurus, which are smaller in size, are more generalist than larger species, while C. tibicen selects heavier shells, and C. antillensis selects lighter shells. Such results may contribute to the understanding of the sympatry among these species, in addition to explaining their ability to face the local hydrodynamism.